2017
DOI: 10.1007/s10689-017-9992-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of NFκB1-94ins/delATTG and NFκBIA-881A/G genes in Egyptian patients with colorectal cancer

Abstract: To assess the association of genetic polymorphisms of NFκB1 and NFκBIA genes with the susceptibility to colorectal cancer (CRC). Subjects included 100 Egyptian patients with CRC (60 males and 40 females) in addition to 85 healthy controls (47 males and 38 females) from the same locality. For all participants, genetic polymorphisms of NFκB1-94ins/delATTG (rs28362491) and NFκBIA-881A/G (rs3138053) were detected by using restriction fragment length polymorphism polymerase chain reaction (RFLP-PCR). CRC patients s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…The mean age of CRC patients in this study was 50.8 ±11.2 years. Youssef et al (2017) and Gado et al (2014) found similar results as they reported that the mean age of CRC Egyptian patients ranged from 50 to 62 years. However, Parkin et al (2005) found that the average age of CRC occurrence was about 65 years in western populations.…”
Section: Discussionsupporting
confidence: 79%
“…The mean age of CRC patients in this study was 50.8 ±11.2 years. Youssef et al (2017) and Gado et al (2014) found similar results as they reported that the mean age of CRC Egyptian patients ranged from 50 to 62 years. However, Parkin et al (2005) found that the average age of CRC occurrence was about 65 years in western populations.…”
Section: Discussionsupporting
confidence: 79%
“…After careful review, we total identified 16 studies for final analysis. 33,[36][37][38][39][40][41][42][43][44][45][46][47][48]…”
Section: Literature Retrieval Resultsmentioning
confidence: 99%